PENGEMBANGAN BAHAN AJAR POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN YANG DIOLAH DENGAN EMPAT TAHAP PENGOLAHAN BAHAN AJAR (ETPBA) - Rustinah, Siti (2014)
This undergraduate thesis that entitle "The development of Teaching Materials of solubility and solubility product constants, Subjects that are Treated with Four Step Processing Teaching Materials (ETPBA)" aims to determine the response of the students and teacher towards teaching materials that are processed with Four Step Processing Teaching Materials (ETPBA). The methods that are used in this research are research and development methods. The subject of this research in the form of teaching materials from solubility and solubility product constants that has been processed with Four Step Processing Teaching Materials (ETPBA). The instruments that are used for instance, a questionnaire in the form of content eligibility of criterion test, presentation materials, graphics, language, and the readability of the teaching materials. The procedure of data collection is conducted by administering the teaching materials to students and teachers, and then the student filling the questionnaire form of the readability aspect and for the teacher is given the eligibility of the teaching materials and instruments. Overall, the results show the percentages of the student' perception average to the questionnaire, that relatively the readability of teaching materials from solubility and solubility product constants has an easy criterion to understand by the student with 59,32%. And the teacher perception regarding this material has a good criterion. Keywords: Teaching Materials, Four Stages Processing Teaching Materials (ETPBA), Solubility and solubility product constants. Skripsi yang berjudul "Pengembangan Bahan Ajar Pokok Bahasan Kelarutan dan Hasil Kali Kelarutan yang Diolah dengan Empat Tahap Pengolahan Bahan Ajar (ETPBA)" ini bertujuan untuk mengetahui tanggapan siswa dan guru terhadap bahan ajar yang diolah dengan Empat Tahap Pengolahan Bahan Ajar (ETPBA). Metode yang digunakan dalam penelitian ini adalah metoda Penelitian dan Pengembangan (Research and Development). Subjek penelitian berupa bahan ajar kelarutan dan hasil kali kelarutan yang telah diolah dengan Empat Tahap Pengolahan Bahan Ajar (ETPBA). Istrumen yang digunakan berupa angket format uji kriteria kelayakan isi, penyajian materi, grafika, bahasa, dan keterbacaan bahan ajar. Prosedur pengambilan data dilakukan dengan pemberian bahan ajar kepada siswa dan guru, kemudian pengisian angket berupa aspek keterbacaan untuk siswa dan instrumen kelayakan bahan ajar yang diberikan kepada guru. Secara keseluruhan keterbacaan bahan ajar kelarutan dan hasil kali kelarutan memiliki kriteria mudah dipahami siswa dengan presentase sebesar 59,32%. Tanggapan guru tentang kelayakan bahan ajar siswa pokok bahasan kelarutan dan hasil kali kelarutan yang diolah dengan Empat tahap Pengolahan Bahan Ajar, memiliki kriteria baik. Kata Kunci: Bahan Ajar, Empat Tahap Pengolahan Bahan Ajar (ETPBA), Kelarutan dan Hasil kali Kelarutan